Implications of Leadership Subterfuge on Collective Bargaining and Organisational Crisis Management. A Case of Nigeria Public Universities (Global Journal of Management and Business Research, 2022)
This study had as its broad objective to examine the implications of leadership subterfuge on collective bargaining and organisational crisis management in Nigeria public domain, with the public universities focal point of analysis. The study adopted the descriptive research design based on the survey method. The conflict theory propounded by Karl Marx was employed as the theoretical framework of analysis for exploring the nexus between leadership subterfuge, collective bargaining, and organisational crisis. The study made use of primary data sourced through structured questionnaire administered via Google online platform that enabled the researchers to access public university lecturers across Nigeria, in a pandemic era where face-to-face survey is inhibited. Secondary data were sourced from published academic journals, conference papers, newspaper articles, and other relevant materials on the internet. Data obtained from the survey were analysed and presented in frequency distribution tables with their corresponding percentages. Findings revealed that there is a significant relationship between leadership subterfuge, collective bargaining, and organisational crisis management in Nigeria public universities; those memorandums of understanding are reached and signed regarding conditions of employment and the better functioning of the university system, but government renege in keeping to the agreements. The study recommended amongst others, that the Legislature should device effective instrument that would ensure management is compelled to recognize employees and their Union(s) in collective bargaining, and to see that the act of non-compliance is handled as a criminal offence. The study summed up that if proactively and properly applied, collective bargaining can serve as the quintessential instrument for managing crisis in the organisation, to enhance harmonious industrial relations and service delivery.
Keywords: leadership styles; leadership subterfuge; collective bargaining; organisational crisis